An Evidence-Based Study on Medicinal Plants for Hemorrhoids in Medieval Persia - Mohammad Hashem Hashempur MD, PhD; Fatemeh Khademi MSc; Maryam Rahmanifard MSc; Mohammad M. Zarshenas PharmD, PhD (SAGE Publishing, 2017)
Hemorrhoids is one of the most common gastrointestinal diseases. There are several therapeutic options associated with some complications. Therefore, researchers look for traditional medicines as a potential resource for introduction of new natural drugs. The current study reports an evidence-based review of herbal remedies for hemorrhoids in traditional Persian medicine. A comprehensive survey about hemorrhoids on the most important manuscripts of traditional Persian medicine was done. Then, scientific data banks were searched for possible related properties of each herb in the conventional medicine. We reported some historical aspects of traditional Persian medicine view on classification, examination, and predisposing factors of hemorrhoids. In addition, we have reported 105 medicinal plants belonging to 51 families. More than half of the reported herbs exhibited anti-inflammatory and analgesic effects. Although lack of human studies regarding the mentioned herbs is noted, positive results from experimental findings can be considered for new drug discovery supported by traditional and medieval experiences.